Gallows view : the first inspector Banks novel - Robinson, Peter, 1950- (New York : Harper Paperbacks, 2010)
"This is the first book in series featuring Yorkshire Detective Inspector Alan Banks, in a new trade paperback edition"--Provided by publisher.
Keywords: Banks, Alan (Fictitious character) -- Fiction; Police -- England -- Yorkshire -- Fiction; Yorkshire (England) -- Fiction